Pemberdayaan Masyarakat Perdesaan Melalui KKN Kolaboratif di Desa Cigobang Kabupaten Cirebon Jawa Barat - Wartoyo Wartoyo; Muhammad Irfai Mulsim; Esta Melandari; Soulthan Akbar Farrakhan; Azzahra Septia Hanami (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
EMPOWERMENT OF RURAL COMMUNITIES THROUGH COLLABORATIVE KKN IN CIGOBANG VILLAGE, CIREBON REGENCY, WEST JAVA. Islamic universities have an obligation to implement the Tridharma of Higher Education, namely research and service education. However, of these three obligations, the service aspect often receives less attention than the education and research aspects. So, the existence of a service program in the form of Collaborative KKN is one form of effort to improve aspects of service that are lagging behind. So this Collaborative KKN Service Program aims to: (1) analyze the effectiveness of village community empowerment programs in increasing community capacity and welfare, (2) identify factors that influence the success of implementing empowerment programs at the village level, (3) formulate adaptive empowerment strategies and sustainable according to local characteristics. The results of this research show that there is still a high level of people who do not understand (literate) the importance of education for their children so that educational outreach needs to be carried out, apart from that there is still low public awareness of environmental cleanliness so that waste management programs need to be implemented, and finally there is still a large social and economic gap that makes It is important to implement mentoring programs and strengthen the community's economy through workshops and local economic innovation.